2021
DOI: 10.1016/j.adro.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Salvage and Systemic Therapies for Recurrent Prostate Cancer as a Result of 18F-DCFPyL PET/CT Restaging

Abstract: Purpose Our purpose was to investigate the effect of the addition of prostate-specific membrane antigen (PSMA)-targeted positron emission tomography/computed tomography (PET/CT) in patients with recurrent prostate cancer post-primary radiation therapy. Methods and Materials A prospective, multi-institutional clinical trial evaluated 2-(3-{1-carboxy-5-[(6-[18F]fluoro-pyridine-3-carbonyl)-amino]-pentyl}-ureido)-pentanedioic acid ( 18 F-DCFPyL) P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 17 publications
0
12
2
Order By: Relevance
“…Patient management after imaging in the PICS trial was previously reported [20]. In this subset of men with isolated local recurrence, within 6 months of imaging, 4 men received focal salvage high dose-rate brachytherapy (sHDR) without ADT (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Patient management after imaging in the PICS trial was previously reported [20]. In this subset of men with isolated local recurrence, within 6 months of imaging, 4 men received focal salvage high dose-rate brachytherapy (sHDR) without ADT (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Also, studies have shown that imaging and biopsy results can evolve post-radiation (9,10). While PSMA PET/CT is well studied for the detection of extra-prostatic recurrence with known sources of false positives, there is little information regarding serial changes in PSMA-avid disease on PET/CT after primary radiation and the relationship of these changes to intra-prostatic control are unknown (11,12). Until larger studies become available, we suggest caution in interpreting isolated local (prostate gland) recurrence detected on PSMA PET/CT at early time points (less than 2-3 years) post radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In those with baseline PSA levels < 0.5 ng/mL, the median CLR was 73% and in those with a baseline PSA level of ≥ 5 ng/mL, the median CLR was 96%. The detection rate rose with increasing PSA levels (from 36% in those with baseline In men with recurrence of prostate cancer, piflufolastat F 18 PET/CT provided clinically meaningful information for subsequent management [35][36][37][38][39]. Changes in treatment intent (65.5%), disease stage (65.5%) and management plans (87.3%) occurred in most patients following piflufolastat F 18 PET/CT in a prospective phase 2 trial (NCT02899312) in 130 patients with biochemical recurrence of prostate cancer after radical prostatectomy or curative-intent radiotherapy [35] Preliminary results from the first 410 patients enrolled in a prospective phase 2 registry study (NCT03718260) suggested that the use of piflufolastat F 18 PET/CT scans to detect disease recurrence in men with low volume metastatic prostate cancer frequently changed intended disease management [36].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…In addition, the pre piflufolastat F 18 PET/CT proposed management plan was modified in 59% of patients as a result of piflufolastat F 18 PET/CT restaging. The median PSA level at relapse was 4.8 ng/mL [37,38]. In patients with biochemically recurrent hormonesensitive prostate cancer after definitive treatment, restaging using piflufolastat F 18 PET/CT led to a change in intended management in 41% of patients (103/253) in a retrospective study in the Netherlands.…”
Section: Pharmacokineticsmentioning
confidence: 99%